Urgensi Pemberdayaan Tanah Wakaf Muhammadiyah Di Wilayah Bengkulu - Sawati Sawati; Amrizal Amrizal (Jurnal Ilmiah Ekonomi Islam, 2023)
This research method uses descriptive qualitative, collective data by conducting in-depth interviews with the chairman and deputy chairman of the Pimpinan Wilayah Muhammadiyah and leadership and deputy leadership of the Majelis Wakaf dan Kehartabendaan. Qualitative data analysis using the Nvivo12 Plus software. The results of the study prove that the management of waqf land assets in PWM Bengkulu, in general, has been going well starting in terms of planning, coordinating, implementation, and supervision even though there are obstacles that are encountered in the field, while in the context of monitoring the management of Muhammadiyah waqf asset,s it is supervised by each assembly concerned and an internal audit is also carried out by the MuhammadiyahCentral Leadership LPPK. Waqf land in the Muhammadiyah Bengkulu area has been used mostly for da'wah activities with facilities for building mosques, education consisting of Kindergarten Schools to Universities, the Health Sector byestablishing hospitals, the social sector planning for the establishment of a Jumpo Home and productive waqf in the form of leasing land and 3 shophouses. The problems or challenges faced by PWM Bengkulu in managing waqf assets are quite dynamic, among them there are still uncertified waqf asset lands.